Mempertimbangkan Waktu Kemunculan Hadis dalam Penggunaannya sebagai Bayan Al-Quran untuk Istimbath Hukum - Maizuddin Maizuddin; Abd. Wahid; Tarmizi M. Jakfar (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This article aims to examine the hadiths used by the majority of scholars from the perspective of the emergence of hadiths to be used as bayan of the Koran in the inheritance of kalalah by conducting a literature review of ushul fiqh works, interpretations and explanations of hadiths. This is based on the decisions of several religious courts in Indonesia which stipulate that the existence of daughters hinders siblings from obtaining inheritance. This ruling is different from fiqh which in no way makes having a daughter hinder siblings from obtaining an inheritance based on the hadith used in interpreting the Koran. The results of this study show that consideration of the time of appearance (wurud) of hadith has become the practice of Sunni scholars in legal istinbath, but is not applied to the function of bayan of the Koran. While the Prophet made legal decisions based on the verses of the Koran that had been revealed to him. On the other hand, it can be seen that the inheritance system built by the Qur'an is carried out gradually in four stages with the revelation of verses within a span of six years, each of which stipulates certain aspects of inheritance law. The use of these hadiths is seen as inappropriate because the hadiths have lost the spirit of renewal that the Qur'an has made. The context of the verses that were revealed later was different from the verses that were revealed earlier. The hadith is only appropriate to use as bayan verses 11 and 12 of sura al-Nisa' which explain their respective parts, not to explain the meaning of kalalah. Abstrak: Artikel ini bertujuan untuk menelaah hadis yang digunakan oleh jumhur ulama dari sisi pertimbangan waktu munculnya hadis untuk digunakan sebagai bayan Alquran dalam kewarisan kalalah dengan melakukan telaah literatur dari karya-karya ushul fiqh, tafsir dan syarah hadis. Hal ini didasari adanya putusan beberapa pengadilan agama di Indonesia yang menetapkan keberadaan anak perempuan menghalangi saudara dalam memperoleh warisan. Putusan ini berbeda dengan fikih yang sama sekali tidak menjadikan adanya anak perempuan menghambat saudara dalam memperoleh warisan berdasarkan hadis yang digunakan dalam menafsirkan Alquran. Hasil telaahan tersebut memperlihatkan bahwa pertimbangan waktu kemunculan (wurud) hadis telah menjadi praktik ulama Sunni dalam istinbath hukum, tetapi tidak diterapkan untuk fungsi bayan Alquran. Sementara Nabi membuat keputusan-keputusan hukum didasarkan atas ayat Alquran yang telah diturunkan kepada beliau. Di sisi lain, terlihat bahwa sistem kewarisan yang dibangun Alquran dilakukan secara gradual dalam empat tahap dengan turunnya ayat dalam rentang waktu enam tahun yang masing-masingnya menetapkan aspek-aspek tertentu hukum kewarisan. Penggunaan hadis-hadis tersebut oleh jumhur ulama dipandang tidak tepat karena hadis-hadis telah kehilangan semangat pembaruan yang telah dibuat Alquran. Konteks ayat yang turun kemudian telah berbeda dengan ayat yang turun terlebih dahulu. Hadis tersebut hanya tepat digunakan sebagai bayan ayat 11 dan 12 surat al-Nisa’ yang menjelaskan bagian masing-masing, tidak untuk menjelaskan makna kalalah.